Entrepreneurial Motivation: Kunci Ketangguhan Wirausaha Perantau Asal Minangkabau - Arifatul Husna; Zarina Akbar; Herdiyan Maulana; Mira Ariyani (Universitas Ciputra Surabaya, 2026)
Minangkabau people migrate to pursue entrepreneurial opportunities. Becoming an entrepreneur in a foreign land is not without various challenges, whether from an economic, environmental, or cultural perspective. Entrepreneurs who can navigate these challenges tend to have a resilient personality, driven by their entrepreneurial motivation. This study aims to examine the extent to which entrepreneurial motivation influences the hardiness of Minangkabau migrant entrepreneurs. The research employs a quantitative method using nonlinear quadratic regression analysis. The respondents in this study consisted of 96 participants selected through purposive sampling. Data were collected using the Entrepreneurial Motivation Scale and the Dispositional Resilience Scale: A Short Hardiness Scale. The results indicate that entrepreneurial motivation significantly influences the hardiness of Minangkabau migrant entrepreneurs, as shown by an R2 value of .505. This means that entrepreneurial motivation contributes 50.5% to the hardiness of Minangkabau migrant entrepreneurs.